2021
DOI: 10.3389/fpubh.2021.687675
|View full text |Cite
|
Sign up to set email alerts
|

“This Graft-vs.-Host Disease Determines My Life. That's It.”—A Qualitative Analysis of the Experiences and Needs of Allogenic Hematopoietic Stem Cells Transplantation Survivors in Germany

Abstract: Background: Allogeneic hematopoietic stem cell transplantation (alloHSCT) is the only curative treatment modality for many patients affected by hematologic malignancies. However, it can cause debilitating long-term effects. Understanding the impact of alloHSCT on all aspects of the patients' life is required for optimal survivorship management.Aim: To explore in-depth HSCT-survivors' experiences and needs post-transplant. Partners were included to provide further information on survivors' needs and how care co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 87 publications
(109 reference statements)
1
22
0
Order By: Relevance
“…With the help of our revised Myeloma Comorbidity Index (R-MCI) we could show that quality of life may not necessarily be impaired after allo-SCT, probably because a reduction of illness-induced limitations may outweigh therapy-associated impairment [ 17 , 46 ]. However, long-term side effects of allo-SCT widely vary between individual patients and have to be seen as a dynamic process with changing burden of symptoms [ 47 ]. Thus, depending on the timepoint of symptom assessment, the rate of chronic GvHD of any grade ranges from 22% to 67% in different trials [ 17 , 24 , 37 , 44 , 48 , 49 ].…”
Section: Allogeneic Transplantation In Newly Diagnosed and Relapsed And/or Refractory Myelomamentioning
confidence: 99%
“…With the help of our revised Myeloma Comorbidity Index (R-MCI) we could show that quality of life may not necessarily be impaired after allo-SCT, probably because a reduction of illness-induced limitations may outweigh therapy-associated impairment [ 17 , 46 ]. However, long-term side effects of allo-SCT widely vary between individual patients and have to be seen as a dynamic process with changing burden of symptoms [ 47 ]. Thus, depending on the timepoint of symptom assessment, the rate of chronic GvHD of any grade ranges from 22% to 67% in different trials [ 17 , 24 , 37 , 44 , 48 , 49 ].…”
Section: Allogeneic Transplantation In Newly Diagnosed and Relapsed And/or Refractory Myelomamentioning
confidence: 99%
“…Furthermore, participants in our study identified that improving knowledge of the importance of exercise on recovery could be used to incentivise exercise; thus, education should be incorporated to maximise psychological capability. Physical and social opportunity to exercise can be maximised through environmental change [26]; our study suggests flexible structuring of exercise around medical appointments and, on par with Parisek and colleagues (2021), ensuring consistent provision of exercise support from pre-to post-transplant [18]. Regarding motivation to exercise in BMT, our study identified that support from staff, exercise tools and outcome measurement of physical change provided automatic incentive, whilst belief that exercise would provide a sense of control or benefit recovery provided reflective motivation.…”
Section: Discussionmentioning
confidence: 55%
“…There is a paucity of research examining the patient perspective regarding physical activity or exercise in BMT. Qualitative research in BMT has predominantly been in multiple myeloma and/or autologous BMT [14][15][16][17] and that in allogeneic BMT has focused on symptoms rather than participation in an exercise program [18,19]. In allogeneic BMT, patients perceive physical incapacity and/or reduced self-efficacy as key issues post-transplant hence increased access to specialised exercise support is required [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have demonstrated the effects of HSCT on patients' interpersonal relationships and social networks. 44 , 45 Firstly, their social circle shrinks, and some survivors face various challenges like discrimination, career derailment, job insecurity, and mental limitations as a result of their illness. These challenges make them to withdraw from social circles.…”
Section: Discussionmentioning
confidence: 99%